2005
DOI: 10.1590/s0034-89102005000400012
|View full text |Cite
|
Sign up to set email alerts
|

Morbidade psiquiátrica e uso de álcool em gestantes usuárias do Sistema Único de Saúde

Abstract: Resumo ObjetivoInvestigar a relação entre consumo de álcool e problemas emocionais em gestantes, verificando se as gestantes com consumo problemático de álcool (uso nocivo ou dependência) tiveram mais problemas emocionais quando comparadas àquelas cujo consumo não era problemático. Métodos Estudo transversal, observacional, sobre uma amostra clínica de um serviço obstétrico público de Ribeirão Preto, SP. A amostra foi não probabilística, de conveniência, do tipo consecutiva, composta por 450 gestantes. Foram a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
30

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 15 publications
0
21
0
30
Order By: Relevance
“…Thus, the association shown in this study allows us to infer that pregnant women who use alcohol tend to have more depressive symptoms, although the reverse path is also possible, that depression precedes the use of alcohol, that is to say, pregnant women make use alcohol to alleviate the symptoms of depression. 18,19 Considering the negative impact of alcohol consumption during pregnancy, great importance should be given to prevention of problems related to the use of alcohol for both the fetus and the woman, including psychiatric disorders that may be triggered. Contrary to another study, 13 it was also found in the present research that pregnant women who use medications in daily basis are more likely to experience depression during pregnancy, which could be combined with fear of childbirth, since women who manifest this feeling may experience psychic maladjustments and use more medication for this reason.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the association shown in this study allows us to infer that pregnant women who use alcohol tend to have more depressive symptoms, although the reverse path is also possible, that depression precedes the use of alcohol, that is to say, pregnant women make use alcohol to alleviate the symptoms of depression. 18,19 Considering the negative impact of alcohol consumption during pregnancy, great importance should be given to prevention of problems related to the use of alcohol for both the fetus and the woman, including psychiatric disorders that may be triggered. Contrary to another study, 13 it was also found in the present research that pregnant women who use medications in daily basis are more likely to experience depression during pregnancy, which could be combined with fear of childbirth, since women who manifest this feeling may experience psychic maladjustments and use more medication for this reason.…”
Section: Discussionmentioning
confidence: 99%
“…Não foram encontrados outros estudos que abordem esta associação. Alguns trabalhos avaliam o consumo de bebida alcóolica entre gestantes com estresse, sintomas depressivos e ansiosos 39,40 , porém não abordam a associação desse hábito com a relação mãe-filho.…”
Section: Discussionunclassified
“…13 A total of 450 women participated in this study and they were all in their last trimester of pregnancy, under pre-natal care and not at risk. The data collection was carried out with women who used the prenatal care of the maternity hospital that attends pregnant women from the SUS in the city of Ribeirão Preto, in the state of São Paulo, in 2001.…”
Section: Methodsmentioning
confidence: 99%
“…18 Recent publications have pointed out the alcohol consumption problem among Brazilian pregnant women, as well as the relation between alcohol consumption and psychiatric symptoms during pregnancy. 13 In Brazil, pre-natal assistance still lacks development of reliable routines and instruments that help healthcare professionals in actions of prevention and diagnosis of the problems related to alcohol consumption. An adequate assessment of alcohol consumption during pregnancy is an essential condition to prevent Fetal Alcohol Syndrome and the late effects of neurological development in children of pregnant women who have consumed alcohol.…”
Section: Introductionmentioning
confidence: 99%